Friendship, flattery, and frankness of speech: studies on friendship in the New Testament world - Fitzgerald, John T. (Novum Testamentum / Supplements, 1996)
This volume deals with the topics of friendship, flattery, and frankness of speech in the Greco-Roman world. The three topics were often related, with candor or frank criticism viewed as the trait that distinguished the true friend from the flatterer. The book's eleven essays are divided into three parts. The first part introduces the volume and discusses the three topics in the thought of Philodemus and Plutarch. Part two deals with Paul's use of friendship language in his correspondence with the Church at Philippi. Part three examines the concept of frankness (parrhesia) in Paul, Luke-Acts, Hebrews, and the Johannine corpus. The volume will be particularly useful to NT Scholars, classicists, and modern theologians and ethicists who are interested in the theory and practice of friendship in antiquity.